PENERAPAN ARSITEKTUR BERKELANJUTAN DALAM PERANCANGAN PUSAT PENELITIAN PERTANIAN DI KABUPATEN GOWA: Rizaldy Nodjeng,Alfiah,Ajwad Muzdar - Nodjeng, Rizaldy; Alfiah, Alfiah; Muzdar, Muhammad Ajwad (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2025)
The design of the Agricultural Research Center applies the concept of a sustainable architecture approach. According to Kamionka (2019), sustainable architecture must be understood as architecture that is implemented in accordance with the principles of sustainable development and standards set by taking into account all issues related to integration and the environment, energy efficiency, water and waste management, material efficiency and raw material management, local preferences, and comfortable and quality use. In designing an agricultural research center, attention must be paid to designs that can meet human needs in terms of physical and mental comfort, safety, and aesthetics that can create connections so that they can generate profits for the sustainability of the building in terms of function or long-term maintenance.